SPACES AND PHYSIOGNOMIES OF EVERYDAY LIFE IN THE ARCHIPELAGO OF CHILOÉ (CHILE), S. XIX - León León, Marco Antonio (2015)
By studying three aspects of everyday life in the archipelago of Chiloé in the nineteenth century, relating to the form and characteristics of their cities, homes and population, the constraints are set to the same geography of the area printed in lifestyles. The accounts of explorers and travelers, not only corroborate this impression, but also constitute the main source to delve into the study of identity, although the islanders built externally, and endorsed further settled discursively over the years, becoming more apparent retention factors before the change in this particular geographical and human scenario.